Phenomenology of space and virtual reality. An experimental course for students in architecture (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
The paper presents the theoretical assumptions and the way of conducting an experimental course on the Phenomenology of Space designed for architects and interior designers.The course made use of virtual reality to allow students to directly experience the perceptive and cognitive effects induced by the forms of space, colour, the texture of materials, and light. Virtual reality was also the medium that made it possible to translate certain philosophical concepts related to the phenomenology of space into an experiential and applicative field close to the sensitivity and spatial culture of the designers.The themes addressed gave rise to a progressive development that allowed students to develop an increasingly complex project and experiment with increasingly complex issues. The course began with the phenomenology of thresholds, and continued with the analysis of field and synesthesia, the phenomenology of atmospheres, and the analysis of orientation and mind maps. In each of these areas of research and experimentation, the common thread remained the relationship between the body and space. The article also presents the exercises proposed to the students and an overall assessment of the teaching experience.
Keywords: Phenomenology; Virtual reality; Achitecture; Philosophy; Education